Evaluation of the Association of VDR rs2228570 Polymorphism with Elite Track and Field Athletes’ Competitive Performance - Bulgay Celal; Bayraktar Isık; Kazan Hasan Huseyin; Yıldırım Damla Selin; Zorba Erdal; Akman Onur; Ergun Mehmet Ali; Cerit Mesut; Ulucan Korkut; Eken Özgür; Ceylan Halil Ibrahim; Badicu Georgian; et al. (Healthcare MDPI, 2023)
The present study aimed to examine the vitamin D receptor (VDR), rs2228570 polymor- phism, and its effect on elite athletes’ performance. A total of 60 elite athletes (31 sprint/power and 29 endurance) and 20 control/ physically inactive, aged 18–35, voluntarily participated in the study. The International Association of Athletics Federations (IAAF) score scale was used to determine the performance levels of the athletes’ personal best (PB). Whole exome sequencing (WES) was performed by the genomic DNA isolated from the peripheral blood of the participants. Sports type, sex, and competitive performance were chosen as the parameters to compare within and between the groups by linear regression models. The results showed no statistically signiﬁcant difference between the CC, TC, and TT genotypes within and between the groups (p > 0.05). Additionally, our results underlined that there were no statistically signiﬁcant differences for the association of rs2228570 polymorphism with PBs within the groups of the (p > 0.05) athletes. The genetic proﬁle in the selected gene was similar in elite endurance, sprint athletes, and in controls, suggesting that rs2228570 polymorphism does not determine competitive performance in the analyzed athlete cohort.
Keywords: athletics; sprint/power athletes; endurance athletes; VDR; rs2228570 polymorphism